2013
DOI: 10.1186/1471-2458-13-1005
|View full text |Cite
|
Sign up to set email alerts
|

Young smokers and non-smokers perceptions of typical users of plain vs. branded cigarette packs: a between-subjects experimental survey

Abstract: BackgroundIn an attempt to minimize the pack design avenue of communication between tobacco producers and smokers and potential smokers, several jurisdictions, including Norway, have considered regulations on cigarette pack design. The main aim of the current study was to investigate how package design affects young people’s perceptions of typical smokers of some pre-chosen cigarette brands and brand varieties.MethodsBased on data from a web survey among 1022 15–22 year-olds, possible effects of plain packagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…6,19 Plain packaging also contributes to making the image of smoking less positive which has the potential to reduce smoking uptake among adolescents. 22 In addition, harm reduction strategies (e.g. switching from cigarettes to nicotine replacement therapy, snus or e-cigarettes) offer an additional approach that could encourage adults to quit or reduce their smoking.…”
Section: Discussionmentioning
confidence: 99%
“…6,19 Plain packaging also contributes to making the image of smoking less positive which has the potential to reduce smoking uptake among adolescents. 22 In addition, harm reduction strategies (e.g. switching from cigarettes to nicotine replacement therapy, snus or e-cigarettes) offer an additional approach that could encourage adults to quit or reduce their smoking.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship between perceived "smoking sensory experience," tobacco packaging and price is confirmed by previous research showing that cigarette packages that displayed fewer branding design elements (i.e., plain packs), were more likely to be unfavorably perceived by smokers as being "cheap looking," thus reducing the appeal associated with smoking. 8,22,23 Research has also shown that such plain packaging reduces perception of tobacco taste, [24][25][26] while increasing visual attention toward health-warning information. 27 This study is limited by the cross-sectional nature of the data which precludes drawing of causal inferences.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, adolescents describe smokers of plain-packaged cigarettes as less trendy and from lower social classes than smokers of branded cigarette packages. [6][7][8][9][10]20 Similarly, smokers of plain-packaged cigarettes are also described as having an "addictive personality", since they continue to smoke even when the appeal of smoking has been removed along with the branding. 9 Therefore, changes in perceptions about the smokers of plain-packaged cigarettes appear to increase social stigma.…”
Section: Perceptionsmentioning
confidence: 99%
“…Brands can also portray information about the smoker who smokes a certain brand of cigarette, such as sex, personality (eg, sophisticated), and social status (eg, wealthy). [6][7][8][9][10] Moreover, branding influences both smokers and nonsmokers. For example, Gendall et al 11 found that nonsmokers characterize cigarette brands with such adjectives as "sophisticated", "trendy", "professional", etc, and are more likely than smokers to associate positive attributes with familiar brands (ie, brands available for purchase).…”
Section: Introductionmentioning
confidence: 99%